AN INTERNSHIP IN THE GOVERNMENT OFFICES AS A TOOL FOR SAVING ADVANCED MANAGEMENT EXPERIENCE - Orgiets O.N. (Pressing Problems of Public Administration, 2017)
The article is considering the issues of an internship passed by the government of cers as a form of accumulating additional knowledge and skills. The internship of government of cers in the foreign countries is considered. It is proved, that the internship is bene cial both for an internee and for an executive government body where he/she does the internship.